Flow characteristics in a transition duct passing from rectangular section to circular section - Gul, Hasan; Evin, Duygu (Natl Inst Science Communication-Niscair, 2007)
The characteristics of a flow in a transition duct, in which the flow passes from a rectangular cross-section to a circular one, were investigated experimentally. The transition duct had an entry aspect ratio of 0.65 and exit aspect ratio of 1. The experiments were conducted at three different channels which have different lengths. The exit cross-sectional area of the transitional duct was double of the inlet. Reynolds number varied in the range of 2x10(5)-6x10(5). Local pressures and velocities were measured along the duct.
Keywords: Turbulent-Flow